Coincidence Time Resolution of Ultrafast Photomultiplier Tube Coupled with LYSO Crystal. Issue 1 (1st November 2022) - Ma, Lishuang; Sen, Qian; Wu, Qi; Zhu, Yao; Yan, Min; Peng, Shuo; Wang, Zhile
Abstract : This manuscript aims to use two ultra-fast photomultiplier tubes (FPMT) coupled with Lu1.8 Y2 SiO5 :Ce (LYSO) crystals to perform a coincidence time resolution (CTR) test applied to Time of Flight-Positron Emission Tomography (TOF-PET). The FPMT used in this work is a kind of Micro Channel Plate-PMT(MCP-PMT) with rise time of 100ps, TTS of 46ps working in single photon mode. The scintillation light waveform of the LYSO crystal appears "separated" when it is detected by the FPMT. At the same time, it is found that the setting of the timing threshold has a great impact on the results of the time resolution. The waveform processing algorithm is optimized by interpolation, and the acquired waveform is processed by the leading edge timing method. The whole test is carried out under the radiation background of 22 Na, the CTR (sigma) measured by LYSO crystal coupled with FPMT is 40ps.